A yellowing-resistant and highly transparent aliphatic polycaprolactone TPU and a preparation method thereof
By using specific formulas and filler combinations in polyurethane elastomers to form a layer structure, the problem of poor yellowing resistance of polyurethane elastomers is solved, high transparency and good yellowing resistance are achieved, and the anti-ultraviolet radiation effect is enhanced.
Patent Information
- Application Number
- CN202310034930.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-10
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-01-10
AI Technical Summary
The existing polyurethane elastomers have poor anti-yellowing properties, which leads to easily turn yellow after outdoor use. The products are often milky white after adding anti-yellowing fillers, and cannot be used to produce colorless and transparent products.
A yellowing-resistant high transparent aliphatic polycaprolactone TPU is adopted, and its formulation includes polyether polyol, polycaprolactone polyol, isocyanate, chain extender, filler and antioxidant. The filler is composed of ultraviolet absorber, boron nitride nanosheets and single crystal alumina. Through the combination and treatment of these materials, a layer structure that can effectively resist ultraviolet rays is formed.
The high transparency and good yellowing resistance of the TPU are achieved, while improving the anti-UV radiation effect, avoiding yellowing and aging caused by ultraviolet irradiation.
Smart Images

Figure BDA0004048925370000081 
Figure BDA0004048925370000091
Abstract
Description
Technical Field
[0001] The present application relates to the field of plastic processing, and more specifically, to a yellowing-resistant and highly transparent aliphatic polycaprolactone TPU and a preparation method thereof. Background Art
[0002] TPU is a thermoplastic polyurethane elastomer rubber, which is mainly synthesized with diphenylmethane isocyanate, small molecule diols, high molecular diols and other materials; it has high tension, pulling force and good toughness, and is widely used in the preparation of shoe materials, films, adhesives, hoses, wires and other materials.
[0003] However, polyurethane elastomers have poor anti-yellowing properties. After being made into finished products, they will easily change from colorless and transparent to orange-yellow after 60 days of outdoor use. Although some products can improve their UV resistance level by adding anti-yellowing fillers or additives to make their UV resistance level reach 4.5, most of these products are milky white and cannot be used to produce colorless and transparent products.
[0004] Therefore, how to prepare a polyurethane elastomer with good yellowing resistance and high transparency is a problem to be solved. Summary of the invention
[0005] In order to prepare a polyurethane elastomer with good yellowing resistance and high transparency, the present application provides a yellowing-resistant and highly transparent aliphatic polycaprolactone TPU and a preparation method thereof.
[0006] In the first aspect, the present application provides a yellowing-resistant and highly transparent aliphatic polycaprolactone TPU, which adopts the following technical solution:
[0007] A yellowing-resistant and highly transparent aliphatic polycaprolactone TPU is prepared from the following raw materials in parts by weight: 10-20 parts of polyether polyol, 50-65 parts of polycaprolactone polyol, 60-80 parts of isocyanate, 5-12 parts of chain extender, 5-12 parts of filler, and 0.5-1 part of antioxidant; the filler is composed of an ultraviolet absorber, boron nitride nanosheets, and single-crystal aluminum oxide in a weight ratio of 1:1-2:2-4.
[0008] By adopting the above technical scheme, polycaprolactone polyol, polyether polyol and isocyanate are matched, and the good yellowing resistance and high transparency of polycaprolactone polyol are utilized, so that the finished TPU has good yellowing resistance and high transparency; the single crystal aluminum oxide, boron nitride nanosheets and ultraviolet absorber in the filler reflect, refract and absorb ultraviolet rays in turn, thereby further improving the anti-ultraviolet radiation effect of the finished product, and the filler is not easy to affect the transparency of the finished product, thereby ensuring that the finished TPU has good yellowing resistance under the condition of high transparency.
[0009] The ultraviolet absorber, boron nitride nanosheets and single crystal alumina are matched with each other. The single crystal alumina is used as the outer layer of the filler. The two-dimensional planar structure of the single crystal alumina is used to reflect ultraviolet rays, thereby reducing the ultraviolet rays that penetrate the finished material. Then, the pore spacing between the ultraviolet absorber and the single crystal alumina and the large specific surface area of the boron nitride nanosheets are combined to perform multi-layer reflection and refraction of ultraviolet rays. Finally, the ultraviolet rays are absorbed by the ultraviolet absorber so that the ultraviolet rays can be resisted, blocked and absorbed by the filler on the surface of the finished product, thereby avoiding ultraviolet radiation to the cross-linked network of the polyurethane elastomer as much as possible, thereby avoiding yellowing of the finished product due to ultraviolet radiation as much as possible.
[0010] Preferably, the filler is prepared by the following method:
[0011] Ⅰ Weighing boron nitride nanosheets and placing them in a sodium carboxymethyl cellulose aqueous solution and dispersing and stirring to prepare a primary mixture;
[0012] Ⅱ The primary mixed material is evenly sprayed onto the surface of the ultraviolet absorber and dried to obtain a mixed material;
[0013] Ⅲ Evenly spraying the sodium carboxymethyl cellulose aqueous solution on the surface of the mixture, then soaking and stirring with glycerol, and distilling to remove water to obtain a composite material;
[0014] IV. Mixing and stirring the composite material and the single crystal alumina uniformly, and then placing them in a humid environment for static treatment to obtain a semi-finished product;
[0015] Ⅴ The semi-finished product is dried to obtain the finished filler.
[0016] By adopting the above technical scheme, boron nitride nanosheets are dispersed in a sodium carboxymethyl cellulose aqueous solution, so that the surface of the boron nitride nanosheets is loaded with sodium carboxymethyl cellulose, and the viscosity of the sodium carboxymethyl cellulose aqueous solution is utilized to make the boron nitride nanosheets adhere to the ultraviolet absorber, so as to form a first layer of coating structure in which the boron nitride nanosheets adhere to the surface of the ultraviolet absorber; then, the sodium carboxymethyl cellulose aqueous solution is sprayed on the surface of the mixture, and because sodium carboxymethyl cellulose is soluble in water but insoluble in alcohol, under the moisture absorption and extraction conditions of glycerol, the water adsorbed in the sodium carboxymethyl cellulose aqueous solution is gradually lost, and the sodium carboxymethyl cellulose aqueous solution gradually loses water to form water-insoluble microparticles, and the microparticles are attached. on boron nitride nanosheets and ultraviolet absorbers; finally, when the composite material is mixed with single-crystalline alumina, it is not easy to agglomerate due to the uneven contact between the single-crystalline alumina and the composite material due to the viscosity of sodium carboxymethyl cellulose. After mixing, under humid conditions, the sodium carboxymethyl cellulose particles absorb water again to achieve a bonding effect, so that the surface of the composite material is evenly bonded to the single-crystalline alumina, and finally a finished filler is obtained. The filler is composed of single-crystalline alumina, boron nitride nanosheets and ultraviolet absorbers from the outside to the inside, so that the filler can process ultraviolet rays by reflection, refraction and absorption in turn under ultraviolet irradiation conditions, and try to avoid yellowing and aging of the finished TPU due to ultraviolet irradiation.
[0017] Fillers, polycaprolactone polyols and isocyanates are matched, and the hydroxyl groups in sodium carboxymethyl cellulose on the surface of the fillers are used to facilitate cross-linking with polycaprolactone polyols and isocyanates, thereby further improving the compatible bonding effect of the fillers in TPU, so that the finished TPU has the advantage of high structural density, and the high mechanical strength of the fillers can improve the mechanical strength of the finished material; at the same time, the fillers have good heat resistance, and the high structural density and good heat resistance make it difficult for the finished TPU to turn yellow even if it is irradiated by ultraviolet rays in a hot oxygen environment.
[0018] Preferably, the particle size of the ultraviolet absorber is 40-60 nm, the particle size of the boron nitride nanosheet is 20-40 nm, and the particle size of the single crystal aluminum oxide is 10-20 nm.
[0019] By adopting the above technical scheme, the particle sizes of the ultraviolet absorber, boron nitride nanosheets, and single-crystalline alumina are limited, and the boron nitride nanosheets and single-crystalline alumina are sequentially attached to the surface of the ultraviolet absorber, ensuring that the filler is in contact with the ultraviolet light, and can achieve the effect of first reflection, then refraction, and finally absorption, thereby reducing the impact of ultraviolet rays on the finished TPU, and making the finished TPU have better yellowing resistance; and the nano-scale particle size can make the filler evenly and stably filled in the TPU structure, so that the finished TPU has higher strength.
[0020] Preferably, the ultraviolet absorber is ultraviolet absorber UV-360.
[0021] By adopting the above technical solution, the ultraviolet absorber UV-360 can absorb ultraviolet rays with a wavelength of 300-400nm, while the wavelength of ultraviolet rays that age polyurethane is within the range of 340-410nm. The refraction and reflection of ultraviolet rays by boron nitride nanosheets and single crystal alumina, combined with the absorption of ultraviolet rays by the ultraviolet absorber, can further prevent TPU from aging. In addition, the ultraviolet absorber UV-360 is not easily affected by moisture and glycerol, so that the ultraviolet absorber UV-360 has better aging resistance in the finished TPU.
[0022] Preferably, the single crystal alumina is prepared by modifying nano single crystal alumina with polyethylene glycol.
[0023] By adopting the above technical scheme, nano single crystal alumina, polyethylene glycol, boron nitride nanosheets, ultraviolet absorber, and sodium carboxymethyl cellulose aqueous solution are matched. Since polyethylene glycol is soluble in water but not in alcohol, the polyethylene glycol on the surface of the single crystal alumina is used to match the sodium carboxymethyl cellulose particles on the surface of the composite material. After standing for a period of time under humid conditions, the polyethylene glycol absorbs water and gradually dissolves, and the viscosity increases. The sodium carboxymethyl cellulose particles absorb water and partially dissolve, and the viscosity also increases. The polyethylene glycol and sodium carboxymethyl cellulose are matched to further improve the bonding effect between the composite material and the single crystal alumina, thereby stabilizing the structure of the finished filler. When the filler is mixed with polycaprolactone polyol and isocyanate, the polyethylene glycol hydroxyl group on the surface of the filler and the carboxyl group in the sodium carboxymethyl cellulose are used to further promote the formation of a cross-linked structure, which not only makes the filler more stably dispersed inside the TPU structure, but also can improve the yellowing resistance and mechanical strength of the finished TPU.
[0024] Preferably, the relative humidity of the humid environment is 75-95%, and the static treatment time is 2-5 hours.
[0025] By adopting the above technical solution, the humidity and the static treatment time are limited, so that the sodium carboxymethyl cellulose particles and the polyethylene glycol can gradually absorb moisture and adhere to each other, thereby facilitating the preparation of the finished filler.
[0026] Preferably, the mass fraction of the sodium carboxymethyl cellulose aqueous solution is 0.2-1%.
[0027] By adopting the above technical scheme, the mass fraction of the sodium carboxymethyl cellulose aqueous solution is limited, so that on the one hand, the boron nitride nanosheets and the ultraviolet absorber are more stably bonded, and on the other hand, when placed in a humid environment after washing, the sodium carboxymethyl cellulose can absorb moisture and bond the composite material and the single crystal alumina.
[0028] Preferably, the TPU further comprises 2-8 parts of coated magnesium aluminum spinel.
[0029] By adopting the above technical solution, the magnesium aluminum spinel has higher transparency, strength, good heat resistance and wear resistance, and can give the finished TPU higher transparency, strength and good heat resistance.
[0030] Preferably, the coated magnesium aluminate spinel is prepared by coating the surface of nano magnesium aluminate spinel with water white rosin resin.
[0031] By adopting the above technical scheme, nano magnesium aluminum spinel and water-white rosin resin are combined, and the softening effect of water-white rosin resin in the hot extrusion molding process is utilized to further improve the compatibility of magnesium aluminum spinel with polyether polyols and polycaprolactone polyols, thereby improving the density of TPU structure, so that the finished TPU has better transparency and higher mechanical strength, and has better heat resistance and wear resistance.
[0032] Nano magnesium aluminum spinel and water-white rosin resin are combined to further improve the anti-ultraviolet effect of the finished TPU by utilizing the absorption effect of water-white rosin resin on ultraviolet rays and the refraction effect of nano magnesium aluminum spinel on ultraviolet rays. Even if exposed to outdoor environment, the finished TPU is not easy to turn yellow.
[0033] In a second aspect, the present application provides a method for preparing yellowing-resistant and highly transparent aliphatic polycaprolactone TPU, which adopts the following technical scheme:
[0034] A method for preparing yellowing-resistant and highly transparent aliphatic polycaprolactone TPU comprises the following steps:
[0035] S1, weighing the filler and the polycaprolactone polyol, mixing them evenly, then adding the polyether polyol and continuing to mix, and after mixing evenly, preparing a primary mixture;
[0036] S2, weighing isocyanate, chain extender, and antioxidant, adding them to the primary mixture, mixing and stirring evenly to obtain a mixture;
[0037] S3, the mixed material is melt-extruded to obtain a finished product.
[0038] By adopting the above technical solution, the finished TPU has both good transparency and excellent yellowing resistance.
[0039] In summary, this application has the following beneficial effects:
[0040] 1. Polycaprolactone polyol, polyether polyol and isocyanate are matched, and the good yellowing resistance and high transparency of polycaprolactone polyol are utilized to make the finished TPU have good yellowing resistance and high transparency; the single crystal alumina, boron nitride nanosheets and ultraviolet absorber in the filler reflect, refract and absorb ultraviolet rays in turn, thereby further improving the anti-ultraviolet radiation effect of the finished product, and the filler is not easy to affect the transparency of the finished product, thereby ensuring that the finished TPU has good yellowing resistance under the condition of high transparency.
[0041] 2. Boron nitride nanosheets, sodium carboxymethyl cellulose aqueous solution, ultraviolet absorber, glycerol, and humid environment static treatment are coordinated. When the composite material is mixed with single-crystalline alumina, it is not easy to agglomerate due to the uneven contact between the single-crystalline alumina and the composite material due to the viscosity of sodium carboxymethyl cellulose. After mixing, under humid conditions, the sodium carboxymethyl cellulose particles absorb water again to achieve a bonding effect, so that the surface of the composite material is evenly bonded to the single-crystalline alumina, and finally the finished filler is obtained. The filler is composed of single-crystalline alumina, boron nitride nanosheets and ultraviolet absorber from the outside to the inside, so that the filler can process ultraviolet rays by reflection, refraction and absorption in turn under ultraviolet irradiation conditions, and try to avoid yellowing and aging of the finished TPU due to ultraviolet irradiation.
[0042] 3. Nano magnesium aluminum spinel and water-white rosin resin are combined, and the melt bonding effect of water-white rosin resin in the hot extrusion molding process is utilized to further improve the adhesion stability of magnesium aluminum spinel in the TPU structure, thereby further ensuring the transparency of the finished TPU while making the finished TPU have higher strength, better heat resistance and wear resistance. DETAILED DESCRIPTION
[0043] The present application is further described in detail below with reference to the embodiments.
[0044] Preparation example of single crystal aluminum oxide
[0045] Preparation Example 1: Single crystal aluminum oxide is prepared by the following method:
[0046] Weigh polyethylene glycol 2000, heat and melt it to obtain a polyethylene glycol melt, spray 0.5 kg of the polyethylene glycol melt evenly on the surface of 1 kg of nano single-crystalline alumina, dry and disperse until they are not sticky to each other, and obtain a finished single-crystalline alumina with a particle size of 10 nm.
[0047] Preparation Example 2: This preparation example differs from Preparation Example 1 in that:
[0048] The particle size of the finished single crystal alumina is 20nm.
[0049] Preparation example of filler
[0050] Preparation Example 3: The filler is prepared by the following method:
[0051] Ⅰ Weigh 1.5 kg of boron nitride nanosheets and place them in 2 kg of sodium carboxymethyl cellulose aqueous solution for dispersion and stirring, wherein the particle size of the boron nitride nanosheets is 20 nm and the mass fraction of the sodium carboxymethyl cellulose aqueous solution is 0.5%, to prepare a primary mixture;
[0052] Ⅱ The primary mixed material is evenly sprayed onto the surface of 1 kg of ultraviolet absorber, and after drying, a mixed material is obtained, and the particle size of the mixed material is 80 nm; the ultraviolet absorber is ultraviolet absorber UV-360, and the particle size of the ultraviolet absorber is 40 nm;
[0053] Ⅲ. Spray 1 kg of sodium carboxymethyl cellulose aqueous solution evenly on the surface of the mixture, the mass fraction of the sodium carboxymethyl cellulose aqueous solution is 0.5%, then add 10 kg of glycerol, stir at a speed of 60 r / min for 5 minutes, then stand for 5 minutes, and then remove water by distillation to obtain a composite material;
[0054] IV. The composite material is mixed and stirred evenly with 3 kg of single crystal alumina, and then placed in an environment with a relative humidity of 85% for 4 hours to obtain a semi-finished product; the single crystal alumina is the single crystal alumina prepared in Preparation Example 1;
[0055] The semi-finished product V is dried to obtain a finished filler, and the particle size of the finished filler is 100nm.
[0056] Preparation Example 4: This preparation example differs from Preparation Example 3 in that:
[0057] Ⅰ Weigh 1 kg of boron nitride nanosheets and place them in 1.5 kg of sodium carboxymethyl cellulose aqueous solution for dispersion and stirring, wherein the particle size of the boron nitride nanosheets is 20 nm and the mass fraction of the sodium carboxymethyl cellulose aqueous solution is 0.2%, to prepare a primary mixture;
[0058] Ⅱ The primary mixed material is evenly sprayed on the surface of 1 kg of ultraviolet absorber, and dried to obtain a mixed material;
[0059] Ⅲ. Spray 0.8 kg of sodium carboxymethyl cellulose aqueous solution evenly on the surface of the mixture, the mass fraction of the sodium carboxymethyl cellulose aqueous solution is 0.2%, then add 10 kg of propylene glycol, stir at a speed of 60 r / min for 5 minutes, then stand for 5 minutes, and then remove water by distillation to obtain a composite material;
[0060] IV. The composite material is mixed with 2 kg of single crystal alumina and stirred evenly, and then placed in an environment with a relative humidity of 75% for 5 hours to obtain a semi-finished product;
[0061] Ⅴ The semi-finished product is dried to obtain the finished filler.
[0062] Preparation Example 5: This preparation example differs from Preparation Example 3 in that:
[0063] Ⅰ Weigh 2 kg of boron nitride nanosheets and place them in 2.5 kg of sodium carboxymethyl cellulose aqueous solution for dispersion and stirring, wherein the particle size of the boron nitride nanosheets is 40 nm and the mass fraction of the sodium carboxymethyl cellulose aqueous solution is 1%, to prepare a primary mixture;
[0064] Ⅱ The primary mixed material is evenly sprayed onto the surface of 1 kg of ultraviolet absorber, and after drying, a mixed material is obtained, the particle size of the mixed material is 140 nm; the particle size of the ultraviolet absorber is 60 nm;
[0065] Ⅲ. Spray 1.4 kg of sodium carboxymethyl cellulose aqueous solution evenly on the surface of the mixture, the mass fraction of the sodium carboxymethyl cellulose aqueous solution is 1%, then add 10 kg of propylene glycol, stir at a speed of 60 r / min for 5 minutes, then stand for 5 minutes, and then remove water by distillation to obtain a composite material;
[0066] IV. The composite material is mixed and stirred evenly with 4 kg of single crystal alumina, and then placed in an environment with a relative humidity of 95% for 2 hours to obtain a semi-finished product; the single crystal alumina is the single crystal alumina prepared in Preparation Example 4;
[0067] The semi-finished product V is dried to obtain a finished filler, and the particle size of the finished filler is 180nm.
[0068] Preparation example of coated magnesia-alumina spinel
[0069] The water-white rosin resin in the following raw materials was purchased from the water-white rosin resin produced by Shangrao Sinan Resin Co., Ltd.
[0070] Preparation Example 6: Coated magnesium aluminum spinel is prepared by the following method:
[0071] The resin liquid is obtained by weighing water white rosin resin, heating and hot melting. 0.3 kg of the resin liquid is evenly sprayed on the surface of 1 kg of nano magnesium aluminum spinel, the particle size of the nano magnesium aluminum spinel is 100 nm, and the coated magnesium aluminum spinel is obtained by drying and dispersing until they are not adhered to each other. The particle size of the coated magnesium aluminum spinel is less than 200 nm.
[0072] Example
[0073] Among the following raw materials, polycaprolactone polyol was purchased from PCL210 produced by Jiangsu Haolong Chemical Co., Ltd.; isocyanate was purchased from TDI-100 produced by Tonglan New Energy Technology Development (Shandong) Group Co., Ltd.; other raw materials and equipment were all commercially available.
[0074] Example 1: A yellowing-resistant and highly transparent aliphatic polycaprolactone TPU:
[0075] 16kg of polyether polyol, 60kg of polycaprolactone polyol, 70kg of isocyanate, 8kg of chain extender, 8kg of filler, and 0.8kg of antioxidant; the chain extender is triethanolamine; the filler is the filler prepared in Preparation Example 3, and the antioxidant is antioxidant 1010; the molecular weight of the polyether polyol is 2000;
[0076] The preparation method is as follows:
[0077] S1. Weigh the filler and add it to the polycaprolactone polyol, mix and stir for 20 minutes at a stirring speed of 80 r / min, then add the polyether polyol and continue to mix, and stir for 10 minutes to mix evenly to obtain a primary mixture;
[0078] S2. Weigh isocyanate, chain extender and antioxidant and add them to the primary mixture, continue to mix and stir evenly to obtain a mixture; S3. Place the mixture in a twin-screw extruder, extrude and shape at a screw speed of 120 rpm and a temperature of 170° C. to obtain a finished product.
[0079] Embodiment 2: This embodiment differs from Embodiment 1 in that:
[0080] 10kg of polyether polyol, 50kg of polycaprolactone polyol, 60kg of isocyanate, 5kg of chain extender, 5kg of filler, and 0.5kg of antioxidant; the filler is the filler prepared in Preparation Example 4.
[0081] Embodiment 3: This embodiment differs from Embodiment 1 in that:
[0082] 20kg of polyether polyol, 65kg of polycaprolactone polyol, 80kg of isocyanate, 12kg of chain extender, 12kg of filler, and 1kg of antioxidant; the filler is the filler prepared in Preparation Example 5.
[0083] Embodiment 4: This embodiment differs from Embodiment 1 in that:
[0084] 5 kg of coated magnesium aluminum spinel prepared in Preparation Example 6 was added to the raw materials.
[0085] Embodiment 5: This embodiment differs from Embodiment 1 in that:
[0086] 2 kg of coated magnesium aluminum spinel prepared in Preparation Example 6 was added to the raw materials.
[0087] Embodiment 6: This embodiment differs from Embodiment 1 in that:
[0088] 8 kg of coated magnesium aluminum spinel prepared in Preparation Example 6 was added to the raw materials.
[0089] Embodiment 7: This embodiment differs from Embodiment 1 in that:
[0090] During the preparation of fillers:
[0091] III. Evenly spraying 1 kg of sodium carboxymethyl cellulose aqueous solution on the surface of the mixture, the mass fraction of the sodium carboxymethyl cellulose aqueous solution being 0.5%, to obtain a composite material;
[0092] IV. Mix the composite material and 3 kg of single crystal alumina and stir evenly to obtain a semi-finished product;
[0093] Ⅴ The semi-finished product is dried and dispersed to obtain the finished filler.
[0094] Embodiment 8: This embodiment differs from Embodiment 1 in that:
[0095] During the preparation of the filler: 1.5 kg of boron nitride nanosheets, 1 kg of ultraviolet absorber, and 3 kg of single crystal alumina were weighed and mixed and stirred evenly to obtain the filler.
[0096] Embodiment 9: This embodiment differs from Embodiment 1 in that:
[0097] The single crystal alumina in the filler material is not treated with polyethylene glycol.
[0098] Embodiment 10: This embodiment differs from Embodiment 4 in that:
[0099] The coated magnesia-alumina spinel is replaced by magnesia-alumina spinel of equal mass in the raw material.
[0100] Comparative Example
[0101] Comparative Example 1: The difference between this comparative example and Example 1 is that:
[0102] No boron nitride nanosheets and single crystal alumina are added to the filler raw materials.
[0103] Comparative Example 2: The difference between this comparative example and Example 1 is that:
[0104] No UV absorber and boron nitride nanosheets are added to the filler raw materials.
[0105] Comparative Example 3: The difference between this comparative example and Example 1 is that:
[0106] The filler is silicon dioxide, and the particle size of silicon dioxide is 100nm.
[0107] Comparative Example 4: The difference between this comparative example and Example 1 is that:
[0108] The polycaprolactone polyol is replaced by polyether polyol of equal mass in the raw materials.
[0109] Performance testing
[0110] 1. Yellowing resistance test
[0111] Finished TPUs were prepared by the preparation methods of Examples 1-10 and Comparative Examples 1-4, respectively, and the yellowing resistance grades were tested with reference to HG / T3689-2001, and the grades were recorded.
[0112] 2. Light transmittance detection
[0113] Finished TPUs were prepared by the preparation methods of Examples 1-10 and Comparative Examples 1-4, respectively, and the light transmittance was tested with reference to GB / T2410-2008, and the data were recorded.
[0114] 3. Tensile strength test
[0115] Finished TPUs were prepared by the preparation methods of Examples 1-6, 8-10 and Comparative Examples 1-2, respectively, and the tensile strength was tested according to GB / T529-2008, and the data were recorded.
[0116] Note: In the above test items, only the TPU sample is changed in each test item, and the other test conditions are the same.
[0117] Table 1 Performance test table
[0118]
[0119]
[0120] In combination with Examples 1-3 and Table 1, it can be seen that the finished TPU prepared in the present application has good yellowing resistance and high light transmittance; it indicates that the polycaprolactone polyol, polyether polyol, and isocyanate are matched, and the good yellowing resistance and high transparency of the polycaprolactone polyol are utilized to make the finished TPU have good yellowing resistance and high transparency; the single crystal alumina, boron nitride nanosheets, and ultraviolet absorbers in the filler reflect, refract, and absorb ultraviolet rays in turn, thereby further improving the anti-ultraviolet radiation effect of the finished product, and the filler is not easy to affect the transparency of the finished product, thereby ensuring that the finished TPU has good yellowing resistance under the condition of high transparency.
[0121] It can be seen from the combination of Example 1 and Examples 4-6 and Table 1 that the light transmittance of the finished TPU prepared in Examples 4-6 is greater than that in Example 1, and the tensile strength is greater than that in Example 1; this indicates that the nano-magnesium aluminum spinel and the water-white rosin resin are matched, and the melt bonding effect of the water-white rosin resin in the hot extrusion molding process is utilized to further improve the adhesion stability of the magnesium aluminum spinel in the TPU structure, and the high transparency of the magnesium aluminum spinel is utilized to further ensure the transparency of the finished TPU; and the absorption effect of the water-white rosin resin on ultraviolet rays is combined with the refraction effect of the nano-magnesium aluminum spinel on ultraviolet rays to further improve the anti-ultraviolet effect of the finished TPU, and even if exposed to the outdoor environment, the finished TPU is not easy to turn yellow; at the same time, the combination of nano-magnesium aluminum spinel and the water-white rosin resin can further improve the mechanical strength of the finished TPU.
[0122] It can be seen from Example 1 and Examples 7-10 and Table 1 that during the preparation of the filler in Example 7, the composite material and the single-crystalline alumina are directly bonded by the sodium carboxymethyl cellulose aqueous solution without being treated with glycerol and a humid environment. Compared with Example 1, the yellowing resistance grade of the finished TPU prepared in Example 7 is worse than that in Example 1; this indicates that the mixture, sodium carboxymethyl cellulose solution, glycerol, and humid environment static treatment are coordinated. When the composite material is mixed with the single-crystalline alumina, it is not easy to agglomerate due to the viscosity of sodium carboxymethyl cellulose causing uneven contact between the single-crystalline alumina and the composite material. After mixing, under humid conditions, the sodium carboxymethyl cellulose particles absorb water again to achieve a bonding effect, so that the surface of the composite material is evenly bonded to the single-crystalline alumina, and finally a finished filler is obtained. The filler is composed of single-crystalline alumina, boron nitride nanosheets, and ultraviolet absorbers from the outside to the inside, so that the finished TPU can process ultraviolet rays through reflection, refraction, and absorption of the filler in turn under ultraviolet irradiation conditions, and try to avoid yellowing and aging of the finished TPU caused by ultraviolet irradiation.
[0123] During the preparation of the filler in Example 8, boron nitride nanosheets, ultraviolet absorbers, and single crystal alumina are directly mixed and stirred. Compared with Example 1, the yellowing resistance grade of the finished TPU prepared in Example 8 is worse than that in Example 1, and the tensile strength is less than the tensile strength of Example 1; this indicates that the filler prepared by direct mixing does not form a layer structure, and when mixed with polyether polyols and polycaprolactone polyols, it is easy to disperse separately, and each plays its own role, which is poorer than the superposition effect, thereby easily affecting the yellowing resistance of the finished TPU; and direct mixing does not have the bonding effect of sodium carboxymethyl cellulose, which easily affects the compatibility and bonding of boron nitride nanosheets, ultraviolet absorbers, single crystal alumina with raw materials such as polyether polyols and polycaprolactone polyols, thereby affecting the mechanical strength of the finished TPU.
[0124] The single crystal alumina in the filler raw material of Example 9 has not been treated with polyethylene glycol. Compared with Example 1, the yellowing resistance grade of the finished TPU prepared in Example 9 is worse than that in Example 1, and the tensile strength is less than that in Example 1; this indicates that polyethylene glycol can improve the bonding effect between the single crystal alumina and other raw materials in TPU, thereby making the internal structure density of TPU higher, thereby improving the yellowing resistance of the finished TPU; and under the action of polyethylene glycol, the single crystal alumina can improve the cross-linking density between the single crystal alumina and the internal structural materials of TPU, and the single crystal alumina is located on the surface of the filler, and the single crystal alumina can improve the bonding compatibility between the filler and the raw materials inside the TPU, and cooperate with the cross-linking effect of sodium carboxymethyl cellulose and TPU, which further promotes the stable bonding of the filler in the internal structure of TPU, so that the finished TPU has higher mechanical strength.
[0125] Combining Example 1 and Comparative Examples 1-4 and Table 1, it can be seen that no boron nitride nanosheets and single crystal alumina are added to the filler raw material of Comparative Example 1, and no ultraviolet absorber and boron nitride nanosheets are added to the filler raw material of Comparative Example 2. Compared with Example 1, the yellowing resistance of the finished TPU prepared in Comparative Examples 1 and 2 is worse than that in Example 1; it indicates that the ultraviolet absorber, boron nitride nanosheets and single crystal alumina are matched, and after the ultraviolet rays reach the surface of TPU, the single crystal alumina reflects the ultraviolet rays, the boron nitride nanosheets refract the ultraviolet rays, and the ultraviolet absorber absorbs the ultraviolet rays, so that the finished TPU has a good yellowing resistance effect; and the filler made of boron nitride nanosheets, single crystal alumina and ultraviolet absorber can improve the mechanical strength of the finished TPU.
[0126] The filler in Comparative Example 3 is silica, and the silica particle size is 100 nm. Compared with Example 1, the yellowing resistance of the finished TPU prepared in Comparative Example 3 is worse than that in Example 1, and the transmittance is lower than that in Example 1; this indicates that the refraction, reflection, and absorption effects of silica on ultraviolet rays are worse than those of single crystal alumina, boron nitride nanosheets, and ultraviolet absorbers, thereby affecting the yellowing resistance of the finished TPU and affecting the transmittance of the finished TPU.
[0127] In Comparative Example 4, the polyether polyol of equal mass is used to replace the polycaprolactone polyol in the raw material. Compared with Example 1, the yellowing resistance of the finished TPU prepared in Comparative Example 4 is worse than that in Example 1, which indicates that the polycaprolactone polyol, polyether polyol and isocyanate are matched, and the good yellowing resistance and high transparency of the polycaprolactone polyol are utilized to make the finished TPU have good yellowing resistance and high transparency.
[0128] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A yellowing-resistant and highly transparent aliphatic polycaprolactone TPU, characterized in that: The invention is prepared from the following raw materials in parts by weight: 10-20 parts of polyether polyol, 50-65 parts of polycaprolactone polyol, 60-80 parts of isocyanate, 5-12 parts of chain extender, 5-12 parts of filler, 0.5-1 part of antioxidant, and 2-8 parts of coated magnesium aluminum spinel; the filler is composed of ultraviolet absorber, boron nitride nanosheets and single crystal alumina in a weight ratio of 1:1-2:2-4; the single crystal alumina is prepared by modifying nano single crystal alumina with polyethylene glycol; the coated magnesium aluminum spinel is prepared by coating the surface of nano magnesium aluminum spinel with water white rosin resin; the particle size of the ultraviolet absorber is 40-60nm, the particle size of the boron nitride nanosheets is 20-40nm, and the particle size of the single crystal alumina is 10-20nm; The filler is prepared by the following method: Ⅰ Weighing boron nitride nanosheets and placing them in a sodium carboxymethyl cellulose aqueous solution and dispersing and stirring to prepare a primary mixture; Ⅱ The primary mixed material is evenly sprayed onto the surface of the ultraviolet absorber and dried to obtain a mixed material; Ⅲ Evenly spraying the sodium carboxymethyl cellulose aqueous solution on the surface of the mixture, then soaking and stirring with glycerol, and distilling to remove water to obtain a composite material; IV. Mixing and stirring the composite material and the single crystal alumina uniformly, and then placing them in a humid environment for static treatment to obtain a semi-finished product; Ⅴ The semi-finished product is dried to obtain the finished filler.
2. The yellowing-resistant and highly transparent aliphatic polycaprolactone TPU according to claim 1, characterized in that: The ultraviolet absorber is ultraviolet absorber UV-360.
3. The yellowing-resistant and highly transparent aliphatic polycaprolactone TPU according to claim 1, characterized in that: The relative humidity of the humid environment is 75-95%, and the static treatment time is 2-5 hours.
4. The yellowing-resistant and highly transparent aliphatic polycaprolactone TPU according to claim 1, characterized in that: The mass fraction of the sodium carboxymethyl cellulose aqueous solution is 0.2-1%.
Citation Information
Patent Citations
Structural adhesive
CN114015408A
Self-repairing yellowing-resistant high-transparency aliphatic polyurethane elastomer and preparation method thereof
CN117659339A